Characterization of components of resistance to Corn Stunt disease - Oleszczuk, José Darío (2020)
Corn Stunt is an important disease in the Americas due to it high prevalence and the yield reductions that can cause when present. However, changes in the presence of this disease across years hampers the effective identification of resistant genotypes to this disease. To avoid the limitations of phenotypic selection under natural pressure, this research aimed to devise an effective strategy to screen disease-resistant genotypes in the absence of high and constant natural pressures. To do so, we investigated the presence of antixenosis and antibiosis as components of resistance to the vector Dalbulus maidis as well as resistance to the pathogen Spiroplasma kunkelii under artificial inoculation conditions in four maize hybrids. The hybrids shown differences in their levels of resistance and target organisms, either the insect vector or the pathogen. Antixenosis and antibiosis to D. maidis were observed in DK72-10. Resistance to S. kunkelii by DK79-10 was seen as a delayed onset of symptoms, and DKB390 showed antixenosis to D. maidis and resistance to S. kunkelii. An association between symptom severity and yield reduction was found, but not between accumulation of pathogen S. kunkelii and symptom severity nor yield. In conclusion, the proposed methodology was efficacious and can aid in the screening of resistant genotypes in breeding programs to reduce the impact of Corn Stunt disease, ensuring that hybrids with good resistance level will be planted by farmers whenever disease occurs.